Desentization therapy on allergic “galah” shrimp-induced Swiss Webster male mice - Andreanus A. Soemardji; Setiadi Ihsan (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Desensitization therapy on “galah” shrimp type I-allergy have been studied on male Swiss Webster mice. Induction of type I allergy was done by intradermic injection of 30% of “galah” shrimp extracts an allergen twice within 14 days. Evaluation of allergic respons was evaluated based on active cutaneous anaphylactic reaction. Desensitization therapy was done by injecting the allergen intradermically daily in 3 weeks with gradual increased of the doses. Based on tolerance level to the cutaneos anaphylactic reaction, the result showed that allergic mice were cured, while the therapy to nonallergic mice induced the same allergic reaction.Keywords : Type I- allergic reaction, ”galah” shrimp, active cutaneous anaphylactic reaction, desentization.